2020
DOI: 10.1101/2020.04.22.20071050
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Eosinopenia Phenotype in Patients with Coronavirus Disease 2019: A Multi-center Retrospective Study from Anhui, China

Abstract: Background: Coronavirus disease 19 has become a global unprecedented pandemic infecting more than one millon people, which is declared by WHO as a international public health emergency. Eosinopenia may predict a poor prognosis of COVID-19. However, to date, there is no detailed analysis of the clinical characteristics of COVID-19 patients with eosinopenia. . We described clincial characteristics of patients with COIVD-19 and eosinopenia phenotype. Results:The median age of patients with COVID-19 was 39 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 36 publications
2
6
0
Order By: Relevance
“…16 The median eosinophil count in COVID-19-positive patients included in our study was similar to the median counts in other studies. 3,[11][12][13][14][15] In our study, eosinopenia for early diagnosis of COVID-19 had a sensitivity of 80.68% and specificity of 100%. Li Q et al have reported that eosinopenia has a sensitivity of 74.7% and specificity of 68.7% in separating COVID-19 patients from controls.…”
Section: Discussionsupporting
confidence: 45%
See 2 more Smart Citations
“…16 The median eosinophil count in COVID-19-positive patients included in our study was similar to the median counts in other studies. 3,[11][12][13][14][15] In our study, eosinopenia for early diagnosis of COVID-19 had a sensitivity of 80.68% and specificity of 100%. Li Q et al have reported that eosinopenia has a sensitivity of 74.7% and specificity of 68.7% in separating COVID-19 patients from controls.…”
Section: Discussionsupporting
confidence: 45%
“…The incidence of eosinopenia in COVID-19 patients reported in other studies varies from 50.8% to 94%. 3,[11][12][13][14][15] This difference may be attributed to differences in normal reference intervals. 3,11,15 Although 0 eosinophils have been reported in COVID-19 patients, 12,15 the percentage of patients presenting with 0 eosinophil count has been reported only in much smaller studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, PLR has in COVID -19 patients a better correlation with classical inflammation makes than in other diseases. This could be the consequence of coagulation changes that appear in COVID-19 [22,26,27]. Peripheral bloodcells, eosinophils, in particular, seem to help predict severe disease as they tend to accumulate in infected tissues "to fight" the virus.…”
Section: Plos Onementioning
confidence: 99%
“…Mast cells were 1000-fold higher in BAL of HP patients, and analysis of excessive amounts of histamine in the fluid suggested that the lavage procedure may promote mast cell degranulation [ 29 ]. In this vein, eosinopenia in severe SARS-CoV-2 cases and may suggest migration to the lungs [ 30 ]. Autopsy has confirmed eosinophils in the lung, and restoration of eosinophil counts in the blood are predictive of SARS-CoV-2 resolution by also testing negative via reverse transcription polymerase chain reaction (RT-PCR) signifying viral clearance [ 31 32 ].…”
Section: Immunopathologymentioning
confidence: 99%